Tantangan dan Kompetensi Kunci Desainer Produk Industri dalam Membangun Masa Depan Sepeda Motor Listrik Nasional di Era Teknologi 4.0 - Ardodi, Hendra; Pasaribu, Yannes (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
This research delves into the development of electric motorcycles in Indonesia, examining the historical progression, market potential, and consumer trends among millennials, Gen Z, and Gen Y, while also addressing the competencies industrial product designers require in navigating the challenges posed by the Technology 4.0 disruption era. The study aims to furnish a thorough understanding of the electric motorcycle landscape in Indonesia, pinpoint existing market opportunities, and scrutinize consumer trends within millennial, Gen Z, and Gen Y demographics that are pivotal in driving electric vehicle demand. Additionally, this research seeks to delineate the essential competencies that industrial product designers must possess to effectively develop innovative and sustainable electric motorcycles. The findings of this study highlight a significant market potential for electric motorcycles in Indonesia, particularly among millennials, Gen Z, and Gen Y consumers. In response, industrial product designers need a comprehensive grasp of Technology 4.0, foundational principles of product design, creativity, innovation, sustainability, and digital technology integration. Such competencies are crucial for the successful development of electric motorcycles that align with the preferences and needs of Indonesian consumers. This research provides a foundation for strategic decision-making within the automotive industry as it transitions towards a future that is increasingly sustainable and technologically advanced. Keywords: Electric Motorcycle, Automotive Industry Development, Millennial Generation and Gen Z, Industrial Product Design, Potential Market.